Relación entre el Job Crafting y Engagemet en los colaboradores de la empresa comercial Fox Oriente Iquitos febrero 2025 - Del Aguila Vargas, Martha Deidith (2025)
This study examines the relationship between job crafting (employees' ability to shape their own work) and engagement (their commitment and dedication) at Fox Oriente Iquitos, using data from November 2024. The findings reveal a Spearman correlation of 0.419 (p = 0.021), confirming the validity of the hypothesis. The research shows a high level of job crafting in the organization, with 83% of employees demonstrating a high level and 17% a moderate level. This indicates a proactive workforce, willing to adapt their roles and find greater meaning in their tasks. At the same time, high engagement is observed, with 87% of employees at a high level and 13% at a moderate level. This engagement suggests that employees feel energized and dedicated, possibly enhanced by their ability to engage in job crafting. Although the relationship is strong, the moderate correlation implies that other factors also influence engagement.